Cr/GLC multilayered coating in simulated deep-sea environment: Corrosion behavior and growth defect evolution. (1st August 2021) - Liu, Yingrui; Du, Hong; Zuo, Xiao; Guo, Peng; Liu, Li; Lee, Kwang-Ryeol; Wang, Aiying; Ke, Peiling
Graphical abstract: Highlights: The corrosion behavior of GLC coating at deep-sea is systematic investigated. The corrosion mechanism is different under different hydrostatic pressure. Hydrostatic pressure enhances the diffusion of seawater through the defect. Severe localized corrosion at defects deteriorated the protective property. Abstract: In this work, the corrosion behavior of the multilayered Cr/GLC coating was evaluated in artificial seawater by comparison at an atmospheric pressure (1 atm) and a higher hydrostatic pressure (300 atm). The results revealed that the corrosion resistance of the coating was more favorable at 1 atm, but the hydrostatic pressure deteriorated coating protectiveness significantly by rapidly accelerating seawater diffusion through the growth defect and promoting the exposure of the substrate. The localized corrosion induced by the penetrating defect became more susceptible. This study is helpful to bring forward the significant guideline to fabricate the dense coating for deep-sea applications.